Risk Mitigation Effects for Mudhārabah Financing Accounting Treatment (Case Study at Bank “YIX” in Aceh) - Muslina Muslina; Angga Syahputra (AL-QARDH, 2021)
Mudharabah financing has a high level of risk caused by moral hazard and adverse selection. The existence of these two risks resulted in a simultaneous impact on the reputation and liquidity of the bank “YIX”, thus requiring risk mitigation. On the other hand, the risk mitigation action raises the contradiction of PSAK No. 105 in particular the recognition of financing, profit sharing and expenses. This study was conducted qualitatively by observing the phenomenon at the bank "YIX" and then describing it in the form of a combination of descriptions of the results of interviews, documentation and observations. The results of this study on risk mitigation measures for the accounting treatment of Mudharabah Financing have a negative effect, which is contrary to the statement of PSAK No. 105 Paragraph 12: recognition of mudharabah investments as investments; paragraph 22: does not justify recognizing profits from projected results of operations; paragraph 13 point c: does not allow charging fees without an agreement. If this is not mitigated, then the impact of financing risk will not only affect operations, but also reputation and even the potential for the loss of customers or investors because they are not prepared for the loss of funds due to the comprehensive application of the Mudharabah Financing concept.